The RAND Security Cooperation Prioritization and Propensity Matching Tool - Paul, Christopher; Nixon, Michael; Peterson, Heather; Grill, Beth; Yeats, Jessica (RAND Corporation, 2023)
Recent RAND research identified practices and contextual factors associated with greater or lesser degrees of success in security cooperation. A related diagnostic tool maximizes the utility of these analyses and can help defense planners identify potential mismatches between security cooperation funding, priorities, and propensity for success with a given country.